SEASONAL OCCURRENCE OF PENAEUS SEMISULCATUS DE HAAN, PANULIRUS POLYPHAGUS (HERBST) AND PORTUNUS (P.) PELAGICUS (LINN.) IN THE COCHIN BACKWATER - Rao, P Vedavyasa; Kathirvel, M (Indian Journal of Fisheries, 2011)
Distribution al1d abundance of Penaells selllislilcallls de Haan and Porlll/llls (PorIUl/lls) pelagiclis (Linnaeus) in relation to salinity and temperature variations in Cochin backwater have been studied. These species disappear from this environment in July, when the salinity and the temperature decrease and reappear again in November-December when the values of these factors increase. As compared to the related species of commercial penaeid prawns and portunid crabs occurring in the backwaters, these species to be less euryhaline. The appear interesting phenomenon of occurrence of post-larval stages of the truly marine spiny lobster, POllldims polypflaglls (Herbst) in these estuarine and juvenile waters is also reported here for the first time.